(untitled) (Physical Education, Health and Social Sciences, 2025)
Numerous plants were being used in conventional treatment and for cure of many diseases along with maintaining health from ancient times. Cynodon dactylon, Arundo donax, Alstonia scholaris linn and Plumeria rubra linn have great medicinal importance due to their antioxidant, antidiabetic, antimicrobial, antirheumatic or antihyperlipidemic activities. In this study, extract of aerial parts of C. dactylon , Arundo donax, Alstonia scholaris and Plumeria rubra were prepared in three different solvent via ethyl acetate, methanol and aqueous. Extracts were further processed in order to assess antioxidant, antidiabetic and antimicrobial activity of C.dactylon, A.donax, Alstonia scholaris and Plumeria rubra. Antioxidant activity was assessed by TPC, TFC and DPPH scavenging assay while antidiabetic activity was assessed by Alpha amylase inhibition and glycation analysis. Minimum inhibitory concentration was performed for the determination of antimicrobial activity. Structural characterization were done by Fourier transform infrared spectroscopy (FTIR) and High-performance liquid chromatography (HPLC).Highest yield was obtained by the aqueous extract of P. ruba (10.47%) while lowest yield was obtained by ethyl-acetate extract of C.dactylon and A.donax (0.652%).Highest TPC was observed in Arundo donax aqueous extract (681.27±0.40mg GAE\100g dry weight) while lowest was observed by aqueous extract of Cynodon dactylon (270.83±0.40mg GAE\100g DW). Highest TFC was observed in A. scholaris ethyl acetate extract (807.36.69±0.66mg CE\100g dry weight) while lowest was observed by ethyl-acetate extract of Arundo donax (26.96±0.37mg CE\100g DW). Similarly highest DPPH radical scavenging activity was observed in ethyl acetate extract of P.ruba (77.84±0.33%) while lowest in aqueous extract of A.scholaris (16.96±0.22%). Arundo donax showed highest zone of inhibition against Escherichia coli (15.1±0.94mm) while P.ruba showed lowest zone of inhibition against Staphylococcus aureus (6.0±0.40mm). Highest antiglycation activity was observed in methanolic extract of A.donax (70.20±0.76%) while lowest was observed in ethyl- acetate of C.dactylon (28.40 ±0.15%). Best alpha-amylase activity was observed in methanolic extract of A.scholaris (61.14±0.21%).FTIR analysis of selected plants showed the presence of compounds like alcohol, phenol, carboxylic acid, primary and secondary amides and amines, alkanes, sulphonyl , sulphones, nitro groups, alkyl-halides ,aldehydes, methyl and methylene groups, fluorides, chloride ,alkenes, aromatic compounds ,ether ,ester and anhydrides were observed. HPLC analysis showed the presence of gallic acid, quercetin, caffeic acid, vanillic acid, m-coumaric acid, p-coumaric acid, sinapic acid syringic acid, ferulic acid, benzoic acid and chlorogenic acid. Data was analyzed statistically by using one-way ANOVA and hence it was concluded that a significant difference (p<0.001) was present among extracts made by using different solvents in term of all biological activities.